UPAYA GURU DALAM MENINGKATKAN AKHLAK SISWA DENGAN METODE PENGAWASAN - Adis Herviati; Laela Apri Liani (BADAN PENERBIT STIEPARI PRESS, 2023)
It is very important as a parent to be able to supervise or accompany their child while playing cellphones because giving a child a mobile phone at any time can change the morals of the child. The goal in studying Islamic Religious Education is to become a human being with noble character, this education aims to be able to form a behavior and character in every child and have a strong stance in himself and to educate the life of this nation, the most important role in educating is in the role of parents who can improve / form a character in children and can shape attitudes that is in these children. In this supervision method it is very functional for the teacher because the teacher can pay attention to every behavior - the behavior of his students in order to comply with applicable school regulations, with this supervision the teacher gives full effort to direct his students in good things. To become a teacher is not easy where he must have a strong stance, have character and personality in himself to become a teacher. The teacher is a role model and becomes a role model for each of his students.